Spatio-temporal analysis of land use transformations and their environmental implications in the Thamirabarani River Basin, India - Harani, P.; Gautam, Sneha; Joshi, Suneel Kumar; Ho, Chang-Hoi (Frontiers in Remote Sensing, 2026)
Rapid population growth and associated land-use/land-cover (LULC) transformations exacerbate environmental stress on natural resources, underscoring the importance of continuous monitoring to support sustainable land and water management. This study examines the spatio-temporal dynamics of LULC changes and the interrelationships among LULC, the normalized difference vegetation index (NDVI), land surface temperature (LST), and soil temperature (ST) in the Thamirabarani River Basin in Tamil Nadu, India. Multi-temporal satellite datasets from Landsat-8 (30 m resolution) and Sentinel-2 (10 m resolution) were processed in Google Earth Engine for the period from 2015 to 2024. The change detection analysis presented significant increases in built-up areas (11.6%) and barren land (11.9%), indicating rapid urbanization and progressive land degradation. NDVI analysis showed a significant positive long-term trend across the basin (slope = 0.00055, p = 0.0369), reflecting seasonal and interannual vegetation variability. Although, spatial analysis revealed a stable vegetation condition across the basin, minor reduction in vegetation was observed in urban and degraded areas, where the expansion of built-up and barren land has led to localized vegetation loss. Analyses of LST and ST showed substantial seasonal variations, indicating the critical role of vegetation cover in regulating land-atmosphere energy exchanges. NDVI exhibited a negative correlation with LST (R2 = 0.15-0.55), reflecting the cooling effect of vegetation which reduces surface heating through canopy shading and enhanced evapotranspiration. This suggests that vegetation activity partially controls LST and ST. The present results demonstrate the urgent need to implement integrated, sustainable land and water management strategies, including promoting climate-resilient agricultural practices, regulating urban expansion, and implementing systematic vegetation restoration programs, to maintain ecosystem stability and resilience in the basin under intensifying climatic and anthropogenic pressures.